The slow undoing : the federal courts and the long struggle for civil rights in South Carolina - Lowe, Stephen Harold (University of South Carolina Press, 2021)
"Author Stephen Lowe provides the first comprehensive study of legal action in South Carolina, beginning in the mid-1930s, when Charles Hamilton Houston established the framework for the assault on segregation, and continuing well into the post-Brown era. He situates the study within the historiography of the "Long Civil Rights Movement," demonstrating that both advancement towards, and resistance to, the expansion of African American civil rights began much earlier, and continued much later, than is often recognized within the standard periodization of the movement. African American plaintiffs and lawyers from South Carolina, with support of lawyers from the NAACP Legal Defense and Education Fund, brought and argued civil rights lawsuits in the federal courts of South Carolina attempting to equalize, then desegregate schools, parks, and public life. Meanwhile, White citizens, mostly state politicians and local officials, hired lawyers who crafted new legal theories to defend state practices and forestall Black equality. Over the course of several decades, Blacks and Whites in South Carolina used the courts as a venue within which to contest the Constitutional definitions of justice, equality, and citizenship. Among its contributions, the manuscript expands the dominant narrative of the civil rights movement in South Carolina. While there is a growing literature on the struggle for civil rights in South Carolina, the current project further enhances our ability to understand the many and varied events and individuals who contributed to the struggle in the state. It also explores, in great detail, the extent to which South Carolinians, both black and white, used the courts as a battleground, either to advance racial justice or to delay the implementation of civil rights decisions through new legal and (spurious) sociological arguments respectively. It complicates the "desegregation with dignity" narrative that dominates the popular memory of the civil rights movement in South Carolina. In so doing it helps to answer the question of why the state, which had a long history of often violent repression of African American rights, saw relatively few incidents of the bus burnings and gubernatorial confrontations that marked the period in other states. In South Carolina, Lowe argues, "massive resistance" took place within the context of the federal courts, which were far from uniformly progressive in their rulings around racial equity"-- Provided by publisher.
Based on author's thesis (doctoral - Michigan State University, 1999) issued under title: The magnificent fight : civil rights litigation in South Carolina federal courts, 1940-1970.
Keywords: African Americans -- Civil rights -- South Carolina -- History -- 20th century -- Cases.; Segregation -- Law and legislation -- South Carolina -- History -- 20th century -- Cases.; Federal government -- United States -- Cases.; Noirs américains -- Droits -- Caroline du Sud -- Histoire -- 20e siècle -- Jurisprudence.; LAW / Civil Rights; African Americans -- Civil rights; Federal government; Segregation -- Law and legislation; South Carolina; United States; 1900-1999; Federal courts; History; Trials, litigation, etc.